An Arabidopsis soil-salinity-tolerance mutation confers ethylene-mediated enhancement of sodium/potassium homeostasis. - Jiang, C; Belfield, E; Cao, Y; Smith, J; Harberd, N (2013)
High soil Na concentrations damage plants by increasing cellular Na accumulation and K loss. Excess soil Na stimulates ethylene-induced soil-salinity tolerance, the mechanism of which we here define via characterization of an Arabidopsis thaliana mutant displaying transpiration-dependent soil-salinity tolerance. This phenotype is conferred by a loss-of-function allele of ethylene overproducer1 (ETO1; mutant alleles of which cause increased production of ethylene). We show that lack of ETO1 function confers soil-salinity tolerance through improved shoot Na/K homeostasis, effected via the ethylene resistant1-constitutive triple response1 ethylene signaling pathway. Under transpiring conditions, lack of ETO1 function reduces root Na influx and both stelar and xylem sap Na concentrations, thereby restricting root-to-shoot delivery of Na. These effects are associated with increased accumulation of respiratory burst oxidase homolog F (RBOHF)-dependent reactive oxygen species in the root stele. Additionally, lack of ETO1 function leads to significant enhancement of tissue K status by an RBOHF-independent mechanism associated with elevated high-affinity K(+) TRANSPORTER5 transcript levels. We conclude that ethylene promotes soil-salinity tolerance via improved Na/K homeostasis mediated by RBOHF-dependent regulation of Na accumulation and RBOHF-independent regulation of K accumulation.